Տեղեկություններ հայկական միջնադարյան անկվածի և գորգերի վերաբերյալ (Ըստ ՀՊԹ նյութերի) - Ավանեսյան, Լիլիա (Հայաստանի պատմության թանգարան)
Armenian medieval fabrics and carpets have a special place in the collection of the History Museum of Armenia. They are valuable finds from the city of Ani dating back to the early 13th century: the girl's silk dress/ outfit, the covers of a deceased with gold thread embroidery, the parts of dark red silk fabric, dark brown knotted velvet, woollen carpet, etc. In the group of carpets pile and lint-free fabrics of the 16th – 18th centuries stand out. The decoration and the quality of these objects indicate that they were made in special workshops. According to the sources of the 13th century, those were unions of craftsmen, who acted according to a charter and were called “brotherhoods”. Arabic sources of the 10th – 13th centuries, trade documents of the early 14th century from Cilicia, Turkish accounting documents of the 16th century called “vasikans”, documents of 17th century of “Armenian Trading Company”, trade diaries of merchants of the early 18th century contain the most important information on Armenian expensive fabrics and carpets, the centers of their production and market prices. В коллекции Музея истории Армении особое место имеют средневековые ткани и ковры. Это ценные находки из раскопок города Ани, датируемые началом 13-го в.: детское шёлковое платье, погребальные шёлковые покрывала вышитые золотом, куски темно-красной шёлковой ткани, тёмно-фиолетового петельчатого бархата, шерстяного карпета и т. д. В группе ковров выделяются ворсовые и безворсовые ковры 16 – 18-го вв. Художественное оформление и качественные свойства этих изделий свидетельствуют, что они были изготовлены в специальных мастерских, которые, согласно источникам 13в., были цеховыми объедениниями и назывались «братством». Наиболее важные сведения о дорогих тканях и ковровых изделиях, центрах их производства, о рыночной цене содержатся в арабских источниках 10 – 13-го вв., киликийских торговых документах нач. 14-го в., турецких учётных документах – «васиканах» 16-го в., документах «Армянской торговой компании» 17-го в., торговых дневниках купцов начала 18-го в.
Keywords: Ազգագրություն; Պատկերագրություն